2016
DOI: 10.1038/srep22363
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrogen Sulfide Recruits Macrophage Migration by Integrin β1-Src-FAK/Pyk2-Rac Pathway in Myocardial Infarction

Abstract: Myocardial infarction (MI) triggers an inflammatory reaction, in which macrophages are of key importance for tissue repairing. Infiltration and/or migration of macrophages into the infarct area early after MI is critical for infarct healing, vascularization, and cardiac function. Hydrogen sulfide (H2S) has been demonstrated to possess cardioprotective effects post MI and during the progress of cardiac remodeling. However, the specific molecular and cellular mechanisms involved in macrophage recruitment by H2S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 49 publications
(63 reference statements)
1
35
0
1
Order By: Relevance
“…In a murine MI model subjected to pre- and post-coronary artery occlusion, exogenous H 2 S treatment reduced the recruitment of CD11b + Gr-1 + myeloid cells to the myocardium, inhibited their migration from the splenic reservoir, and decreased serum TNF-α and IL-1β levels, thereby protecting against ischemic myocardial injury ( Zhang et al, 2014 ). Recently, our study demonstrated that exogenous H 2 S treatment increased macrophage infiltration into the infarcted myocardium at the early stage of MI in both wild type and CSE-deficient mice ( Miao et al, 2016b ). In this study, exogenous H 2 S treatment promoted the migration of macrophages in vitro .…”
Section: Myocardial Ischemiamentioning
confidence: 79%
See 1 more Smart Citation
“…In a murine MI model subjected to pre- and post-coronary artery occlusion, exogenous H 2 S treatment reduced the recruitment of CD11b + Gr-1 + myeloid cells to the myocardium, inhibited their migration from the splenic reservoir, and decreased serum TNF-α and IL-1β levels, thereby protecting against ischemic myocardial injury ( Zhang et al, 2014 ). Recently, our study demonstrated that exogenous H 2 S treatment increased macrophage infiltration into the infarcted myocardium at the early stage of MI in both wild type and CSE-deficient mice ( Miao et al, 2016b ). In this study, exogenous H 2 S treatment promoted the migration of macrophages in vitro .…”
Section: Myocardial Ischemiamentioning
confidence: 79%
“…MI and reperfusion injury trigger a complex immune-inflammatory responses in the injured myocardium, including inflammatory leukocyte infiltration and release of cytokines, such as IL-6, IL-8 and TNF-α. Recently, several studies, including our own, have demonstrated that H 2 S plays an important role in immune-inflammatory processes during MI and reperfusion injury ( Elrod et al, 2007 ; Sodha et al, 2009 ; Miao et al, 2016a , b ) ( Figure 2 ). Neutrophils and leukocytes migrate into the infarcted myocardium during the first few hours after the onset of ischemia and peak after 1 day ( Yellon and Hausenloy, 2007 ).…”
Section: Myocardial Ischemiamentioning
confidence: 95%
“…MSCs are characterized by a unique set of membrane molecules involved in adhesion and migration. CD29, which is also known as integrin β1, is highly expressed not only in MSCs but also in macrophages and plays an important role in cell migration [42,43]. CD29 was found to be essential in the trafficking of BM-MSCs to the infarcted myocardium [44].…”
Section: Discussionmentioning
confidence: 99%
“…Incremental studies have reported the involvement of H 2 S in cardiovascular system, central nervous system, and inflammation [ 11 , 39 , 40 ]. Several researches from independent groups have indicated the protective property of H 2 S by preserving mitochondrial function during myocardial infarction [ 41 , 42 ]. Gong et al suggests that H 2 S attenuates lipopolysaccharide-induced cognitive impairment in rats [ 43 ].…”
Section: Discussionmentioning
confidence: 99%